Building Critical Thinking Skills of 21st Century Students through Problem Based Learning Model - Imas Srinana Wardani; Erni Fiorintina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The research was conducted to address the limited critical thinking abilities of fifth-grade students regarding the human respiratory system. This study aims to analyze the influence of the PBL model on the development of critical thinking skills in 21st-century students. This study employed a Quasi Experimental design known as the Non-Equivalent Control Group Design, with a research population of 106 students. The sample consisted of 36 students in class VA (control group) and 33 students in class VB (experimental group). Data collection was performed using a test method comprising five multiple-choice questions and 15 descriptive questions. Data analysis involved assessing normality, homogeneity, and hypothesis tests. The T-Test calculation of the post-test results revealed a significant finding with a Sig. value of 0.000 < 0.05. This significance indicates that the Problem Based Learning model has a positive impact on fostering critical thinking skills in 21st-century students. Implementing the PBL model in science education, particularly in the context of the human respiratory system, falls within the effective category.